(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper presents a comprehensive examination of contemporary Indian English women poets, focusing on their engagement with themes of violence, gender, and identity in the public sphere. Through an in-depth analysis of poets including Mamta Kalia, Imtiaz Dharker, Seeme Qasim, Rukmini Bhaya Nair, and Meena Kandasamy, the study explores how these writers navigate complex sociopolitical landscapes while articulating distinctly female perspectives. The research reveals how their poetry serves as a powerful medium for social critique, challenging patriarchal norms and addressing issues of communal violence, caste discrimination, and professional inequalities. By situating these poets within the broader context of Indian literature and feminist discourse, this paper argues for their significant contribution to both the literary canon and social reform movements in contemporary India.